High-resolution spectroscopy of the blue compact dwarf galaxy Haro 15 : I. Internal kinematics - Firpo, Verónica (2011)
Using echelle spectroscopy, obtained at Las Campanas Observatory, we present a detailed study of the internal kinematics of the nebular material in multiple knots of the blue compact dwarf galaxy Haro15. A detailed analysis of the complex emission-line profiles shows the presence of an underlying broad component in almost all knots, and the brightest star-forming region shows unmistakable signs for the presence of two distinct narrow kinematical components. We also study the information that our analysis provides regarding the motion of the individual knots in the Haro15 galaxy potential, confirming that they follow galactic rotation. Finally, we examine the relation between their velocity dispersion and luminosity, finding that almost all knots follow the relation for virialized systems. This holds for the strong narrow components identified in complex fits and for single profile fits, although the latter show a flatter slope. In agreement with previous findings, in this paper we show that the existence of multiple kinematical components among massive starbursts cannot be overlooked, as it has a noticeable effect on any subsequent analysis that relies on basic parameters.